Africa Agriculture Transformation Scorecard: performance and lessons. Angola - Greffiths, Ikhothatseng Jacob; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso; Fakudze, Bhekiwe; Jordao, K. V. M.; Manuvanga, K.; Pinto, B. (Regional Strategic Analysis and Knowledge Support System for Southern Africa, 2021)
This brief highlights Angola’s performance in the second BR and assesses challenges faced and lessons learned by the country during the review process. The brief also reviews policy and programmatic changes in Angola that can be attributed to the first (2017) and second BRs. It concludes by highlighting required policy actions for Angola to meet the Malabo Commitments by 2025.